Faktor-Faktor Yang Mempengaruhi Kejadian Stunting Di Desa Pabeyan, Kabupaten Indramayu - Yanti Harjono Hadiwiardjo; Citra Ayu Aprilia; Nugrahayu Widyawardani; Tri Faranita; Mila Citrawati; Aulia Chairani (Fakultas Kedokteran Universitas Trisakti, 2026)
Background Malnutrition is frequently referred to as a “silent emergency” by UNICEF. Globally, women and children are particularly vulnerable to health issues related to malnutrition. In Indramayu, the prevalence of stunting was reported at 14.72% in the 2021 Indonesian Nutrition Status Study, indicating a potential increase in malnutrition cases. Risk factors for stunting in developing countries include low birth weight, low maternal education, living in rural areas, short birth length, lack of antenatal care (ANC), incomplete immunisation, and lack of exclusive breastfeeding, based on existing literature. Objective: This study aims to identify factors that may contribute to stunting incidence in Pabean Udik Village, Indramayu Regency. Methods This study employed an observational cross-sectional design. The sample consisted of 32 participants, selected using purposive sampling. Results There was no association between gender, child’s age, preterm birth, maternal education, maternal Body Mass Index (BMI), and family income. (p-value > 0.05). Although among children aged 0–2 years, mothers with a BMI classified as malnourished and family incomes < Rp. 2,000,000 had a higher risk of stunting (RR > 1). Conclusions Although no significant associations were found among the variables studied, stunting remains a public health issue in Indramayu. The lack of a significant association may be due to the small sample size. Further research with a larger sample size is needed to explore other potential risk factors, such as nutritional practices, environmental influences, and access to health services, as well as the importance of collaboration with health services to reduce existing risk factors.